Static and dynamic loading behavior of a hybrid foundation for offshore wind turbines - Chen, Da; Gao, Peng; Huang, Shanshan; Li, Chousheng; Yu, Xiangang (Marine structures, 2020)
Considering the deficiencies of the traditional monopile foundation for offshore wind turbines (OWTs) in severe marine environments, an innovative hybrid foundation is developed in the present study. The hybrid foundation consists of a traditional monopile and a wide–shallow bucket. A series of numerical analyses are conducted to investigate its behavior under the static and dynamic loading, considering various loading eccentricities. A traditional monopile with the same steel volume is used as a benchmark. Although the monopile outperforms the hybrid foundation in terms of the ultimate moment capacity under each loading eccentricity, the latter can achieve superior or the same performance with nearly half of the pile length in the design loading range. Moreover, the horizontal load and moment are mainly resisted by the bucket and the single pile in the hybrid foundation respectively. The failure mechanism of both the hybrid foundation and the monopile is excessive rotation. In the rotation angle of 0.05 rad, the rotation center is located at the depth of approximately 0.6–0.75 times and 0.65–0.75 times the pile length for the hybrid foundation and the monopile respectively. The increasing loading eccentricities can lead to increasing moment bearing capacity, increasing initial stiffness and upward movement of the rotation center of the two foundations, while decreasing load sharing ratio of the single pile in the hybrid foundation. Three scenarios are considered in investigating the dynamic loading behavior of the hybrid foundation. Dynamic response results reveal that addition of the bucket to the foundation can restrain the rotation and lateral displacement effectively. The superiority of the hybrid foundation is more obvious under the combined wave and current loading. •A traditional monopile with the same steel volume is used as a benchmark.•The research focused on some behaviors of innovative hybrid foundations under static loading, such as the load sharing ratio.•The research has been conducted to investigate the performance of innovative hybrid foundations in real marine environments.•A series of numerical analyses are conducted to investigate its behavior under the static and dynamic loading.